2020
DOI: 10.1080/02786826.2020.1763247
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and validation of a hygroscopic growth model with different water activity estimation methods

Abstract: Hygroscopic growth models are currently of interest as aids for targeting the deposition of inhaled drug particles in preferred areas of the lung that will maximize their pharmaceutical effect. Mathematical models derived to estimate hygroscopic growth over time have been previously developed but have not been thoroughly validated. For this study, model validation involved a comparison of modeled values to measured values when the growing droplet had reached equilibrium. A second validation process utilized a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 45 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…H 2 O bound to a fiber will create a localized high RH environment within the fabric even under low RH ambient conditions. For hygroscopic particles, such as NaCl, exposure to RH ≥ 75.3% (deliquescence RH) at 25 °C results in rapid H 2 O adsorption, dissolution, and particle growth, effectively shifting the FE curve to larger D m due to the increase in particle size. Experiments were conducted to test if particle growth impacts the FE using a collection of salts with known deliquescence and RH-dependent growth factors and polystyrene-latex (PSL) and SiO 2 spheres as controls that experience less growth with RH. Figure a shows the FE as a function of time for two of the challenge materials: 305 nm PSL and 305 nm NaCl particles tested on hydrophilic Cotton 10 that was equilibrated at high RH for 12 h. The initial FE of NaCl was 37% and declined with time as the fabric lost H 2 O and returned to the baseline FE after 100 s. Gravimetric measurements after the experiment indicated that the fabric lost all H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…H 2 O bound to a fiber will create a localized high RH environment within the fabric even under low RH ambient conditions. For hygroscopic particles, such as NaCl, exposure to RH ≥ 75.3% (deliquescence RH) at 25 °C results in rapid H 2 O adsorption, dissolution, and particle growth, effectively shifting the FE curve to larger D m due to the increase in particle size. Experiments were conducted to test if particle growth impacts the FE using a collection of salts with known deliquescence and RH-dependent growth factors and polystyrene-latex (PSL) and SiO 2 spheres as controls that experience less growth with RH. Figure a shows the FE as a function of time for two of the challenge materials: 305 nm PSL and 305 nm NaCl particles tested on hydrophilic Cotton 10 that was equilibrated at high RH for 12 h. The initial FE of NaCl was 37% and declined with time as the fabric lost H 2 O and returned to the baseline FE after 100 s. Gravimetric measurements after the experiment indicated that the fabric lost all H 2 O.…”
Section: Resultsmentioning
confidence: 99%
“…After reaching the walls, gases are assumed to partition between the air and the lung tissue according to Henry's law 29,30 . As the gas concentration increases in the tissue, its absorption tends to slow in proportion to its saturation vapor pressure (Raoult's law) 31,32 . The full set of transport equations during inhalation and exhalation are solved to determine the concentrations of vapor in the air and lung tissue during a smoking session.…”
Section: Methodsmentioning
confidence: 99%
“…29,30 As the gas concentration increases in the tissue, its absorption tends to slow in proportion to its saturation vapor pressure (Raoult's law). 31,32 The full set of transport equations during inhalation and exhalation are solved to determine the concentrations of vapor in the air and lung tissue during a smoking session. The mass balance equation for the inhaled vapor in the airway of radial dimension r is given by:…”
Section: Modeling Of Coupled Puff Transport Equations At the Airway S...mentioning
confidence: 99%
“…Because respiratory droplets contain salts, proteins, and carbohydrates, their droplet nuclei are hygroscopic and do not become completely dehydrated (O'Shaughnessy et al., 2020; Vejerano & Marr, 2018). Droplets containing salt evaporate more slowly than pure water droplets, but at isotonic concentrations this difference is negligible (Qu, Escobar, Li, Rao, & Xu, 2020).…”
Section: Transmission Of Covid‐19mentioning
confidence: 99%